Effect of Rat Urine on Ileum Muscle Layer of Bladder Reconstruction: An Experimental Study. (July 2018) - Ersoz, Dilsah; Kirnap, Mahir; Handan Ozdemir, B.; Bacanli, Didem; Haberal, Mehmet
Abstract : Introduction: Renal transplantation is the best possible treatment option for patients with end stage renal failure. Small, bladders with the lack of compliance are one of the causes for kidney failure. Many methods have been tried to solve this problem, but a solution has not been reached. Our aim in this experimental study is to assess the effect of urine on the intestinal muscle layer in a new Ileobladder model and thereby solve bladder problems in the experimental animal model that prevent kidney transplantation. Materials and Methods: A total of 15 Sprague Dawley female rats were enrolled in the study. The bladder was excised 0.5 cm over the urethral orifice. The ileobladder was prepared from 4 cm ileal segment. For pathologic and pharmacologic evaluation the rats re-underwent laparotomy under anesthesia where the ileobladder, the anastomosis site of the ileum and both kidneys were excised. Blood samples of 1 cc were taken from the rats before the first surgery and during the second surgery for the laboratory evaluation of creatinine and urea. When compared both groups had similar measurements before and after the surgeries. Results: The rats were divided into two groups in order to investigate early and late histopathological findings for pathological evaluation. The presence of urothelial metaplasia, presence of inflammation, foreign body reactions, presence of ulcers in mucosa, right and left kidney parenchyma and the rate of inflammation in the renal pelvises were evaluated among groups. In addition, Ileobladder, the small intestine and bladder were compared by measurement of the muscle thickness. Urothelial Metapplasia in group B, inflammation and ulcer development was found to be higher in group A. In group A, the muscle thickness of ileobladder was 0.5 ± 0.78 mm and 0.75 ± 0.8 mm in group B and there was a significant difference in muscle thickness between the two groups. The pharmacological studies showed that in the tissue of ileobladder, the function of muccarinic and beta adrenergic receptors were preserved, and the ileobladder tissue was closer to normal bladder tissue in comparison to ileum tissue in terms of relaxation function. Conclusion: In accordance with all these data, the bladder enlargement surgery can be successfully performed using ileum in rats for experiments. Our new Ileoblader model that we applied in rats is promising to provide functional bladder volume.